1997
DOI: 10.1177/002383099704000405
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic Phrasing and Comprehension

Abstract: From previous research we know that prosodic features are perceptually effective in marking boundaries and that a suitable implementation of these features improves the quality of synthetic speech in terms of acceptability. It can further be assumed that listeners use the perceived prosodic information to compute the meaning of the input speech. This paper, therefore, investigates and determines whether a well-phrased utterance, (that is, an utterance with prosodic boundaries in appropriate positions and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 17 publications
1
28
0
2
Order By: Relevance
“…The finding that both pauses and phrase-final lengthening have a significant effect on the perception of prosodic boundaries is in line with the literature on adult perception of adult speech (e.g. Streeter 1978, Scott 1982, Beach 1991, de Pijper & Sanderman 1994, Sanderman & Collier 1997.…”
Section: Discussionsupporting
confidence: 89%
“…The finding that both pauses and phrase-final lengthening have a significant effect on the perception of prosodic boundaries is in line with the literature on adult perception of adult speech (e.g. Streeter 1978, Scott 1982, Beach 1991, de Pijper & Sanderman 1994, Sanderman & Collier 1997.…”
Section: Discussionsupporting
confidence: 89%
“…For example, in prosodic boundary strength studies in Swedish, Horne (1995) found a strong correlation between pause duration and prosodic boundary strength judgments, but no strong correlation with preboundary length or pitch change. On the contrary, Sanderman and Collier (1997) found that for Dutch listeners, preboundary length is not a crucial cue in the interpretation of prosodic boundary strength, but both pitch change and pause are crucial cues.…”
Section: Discussionmentioning
confidence: 79%
“…In ongoing work, we seek to determine whether this different weighting is also found for infants in different language environments. Some preliminary evidence suggests that Dutch-learning 6-month-old infants, like Dutch adult native speakers (Sanderman & Collier, 1997), weight pause duration more heavily than English-learning infants (Johnson & Seidl, 2005), however, it may be that these infants weight pitch heavily as well. It may be that, given that studies of vowel duration suggest that syllable-timed languages such as Spanish have less variability in vowel duration than stress-timed languages such as English, vowel duration should turn out to be a less important cue in these languages (Ramus, 2002;Ramus, Nespor, & Mehler, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…whether a word is a separate item or describing another; on the whole, context and semantics will ensure that the message is not misleading or unintelligible, but poor chunking prosody is likely to hinder processing; results suggest that this is not likely to be a major problem in ASC. Closer analysis of responses suggests that the most frequent atypical prosodic exponent was a failure to lengthen final syllables to indicate the end of a chunk; final-syllable lengthening has been established as a feature of prosodic delimitation (de Pijper & Sanderman, 1994;Sanderman & Collier, 1997).…”
Section: Communicative Effectiveness In Hfa and As Groupsmentioning
confidence: 99%